Pengaruh Sistem Informasi Akuntansi, Transparansi, Akuntabilitas dan Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan SKPD - Nevani Theresia Sembiring; Yohanes Joni Pambelum; Septa Soraida (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of accounting information systems, transparency, accountability, and internal control systems on the quality of financial reports in Regional Work Units in Palangka Raya City. The type of research used is Explanatory Research with a quantitative approach that uses descriptive quantitative research methods and is assisted by the SPSS program. The results of the study H1, H2 (rejected) and H3, H4, H5 (accepted). Meanwhile, simultaneously, these four variables have been proven to have an influence on the quality of financial reports, which means that improvements in the aspects of accounting information systems, transparency, accountability and internal control will encourage improvements in the quality of the resulting financial reports.